2021
DOI: 10.1136/thoraxjnl-2021-218035
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 environmental contamination from hospitalised patients with COVID-19 receiving aerosol-generating procedures

Abstract: BackgroundContinuous positive airways pressure (CPAP) and high-flow nasal oxygen (HFNO) are considered ‘aerosol-generating procedures’ in the treatment of COVID-19.ObjectiveTo measure air and surface environmental contamination with SARS-CoV-2 virus when CPAP and HFNO are used, compared with supplemental oxygen, to investigate the potential risks of viral transmission to healthcare workers and patients.Methods30 hospitalised patients with COVID-19 requiring supplemental oxygen, with a fraction of inspired oxyg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 36 publications
2
50
0
1
Order By: Relevance
“…Our results demonstrate that in terms of contamination, viability and stability on surfaces and in air samples, the Omicron variant is remarkably similar to previous Covid-19 strains (original and Alpha strains). This correlates with previous studies conducted by us (Ben-Shmuel et al, 2020) and others (Lane et al, 2021;Ong et al, 2021;Thakar et al, 2021;Winslow et al, 2021) in health-care settings, isolation units, quarantine hotels and schools. Moreover, it was recently demonstrated that SARS-CoV-2 significantly loses viability, with near complete viability loss occurring within 2-5 minutes, in controlled laboratory aerosolized dispersion at normal relative humidity (Oswin et al, 2022).…”
supporting
confidence: 91%
“…Our results demonstrate that in terms of contamination, viability and stability on surfaces and in air samples, the Omicron variant is remarkably similar to previous Covid-19 strains (original and Alpha strains). This correlates with previous studies conducted by us (Ben-Shmuel et al, 2020) and others (Lane et al, 2021;Ong et al, 2021;Thakar et al, 2021;Winslow et al, 2021) in health-care settings, isolation units, quarantine hotels and schools. Moreover, it was recently demonstrated that SARS-CoV-2 significantly loses viability, with near complete viability loss occurring within 2-5 minutes, in controlled laboratory aerosolized dispersion at normal relative humidity (Oswin et al, 2022).…”
supporting
confidence: 91%
“…50 Winslow and colleagues measured air and surface environmental contamination with SARS-CoV-2 virus in the room of subjects who received CPAP or HFNC treatment. 51 Compared to those subjects who used conventional oxygen therapy, they did not find any significant differences in the groups receiving CPAP or HFNC treatments. 51 Likewise, Thuresson et al found that the number of positive air samples with SARS-CoV-2 detection was similar in subjects treated with versus without respiratory support (HFNC or NIV).…”
Section: Noninvasive Ventilationmentioning
confidence: 79%
“…An open feasibility study showed that delivery of both HFNO and CPAP can be safely carried out in a HDU in patients with a single organ failure. Ongoing studies suggest that with the use of modified circuits and PPE, dissemination of the infection from CPAP and HFNO devices may be low and ultimately risks depend on the infectivity of patient and specific manoeuvres [143][144][145] .…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…The nature of aerosol generation or dispersion when using CPAP and HFNO has been explored using a range of imaging, particle sizing and virus sampling studies, producing mixed results. [143][144][145] Benefits of CPAP and HFNO should be balanced against risks.…”
Section: Justification Of the Recommendationmentioning
confidence: 99%